Efek Hipoglikemik Pemberian Flake dari Tepung Jagung dan Rumput Laut Gracilaria Sp. pada Tikus Diabetes - Yusasrini, N. L. Ari; T. Darmayanti, Luh Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2017)
The purpose of this study was to determine the hypoglycemic effects of flake made from amixture of corn flour and seaweed Gracilaria sp. (corn flake-seaweed) in diabetic rats.Stage of research began with making of corn flake-seaweed, testing nutritional value offlake and continued with bioassay testing using induced diabetic rats. Twenty-one rats(Wistar) were used in this study. Rats were divided into 3 groups: PS (-), PS (+), and PF.Each group was given a different feed. Analysis was conducted on the analysis of proximateand crude fiber content of flake, blood sugar analysis, weighing and observations in animalfeed consumption. The results showed that flake had 3,62 % of a moisture content, 4,59 %of ash content, 9.30% of protein content, 8,27 % of fat content carbohydrates by differentlevels of 74.22% and 36.54% of crude fiber. Bioassay testing showed that the corn flakeseaweedhas hypoglycemic effects and could lower blood glucose levels by 48.43% indiabetic rats.
Keywords: seaweed; corn; hypoglycemic; flake; diabetes